1989
DOI: 10.1139/z89-407
|View full text |Cite
|
Sign up to set email alerts
|

The phenology and social biology of four sweat bees in a marginal environment: Cape Breton Island

Abstract: Augochlorella striata, Lasioglossum (Evylaeus) cinctipes, Lasioglossum (Evylaeus) comagenense, and Lasioglossum (Dialictus) laevissimum were studied on Cape Breton Island, Nova Scotia, throughout their flight season in 1987. The weather during the summer was unusually good, with above-average temperatures and hours of sunshine but very low rainfall. Conversely, the previous summer had been very poor for bees, with comparatively few days suitable for foraging, particularly in July. Augochlorella striata was bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 8 publications
1
29
1
1
Order By: Relevance
“…This is because the bees nested in small patches of earth amongst stones and rocks directly exposed to incident sunlight. The temperatures and humidities experienced by developing immatures and adults within nests fluctuated markedly (Packer et a!., 1989a The finding of highly significant linkage disequilibrium, even between only two of the loci, is interesting because values of D for allozyme loci are typically close to zero in outbred populations unless the loci are tightly linked (Hedrick, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the bees nested in small patches of earth amongst stones and rocks directly exposed to incident sunlight. The temperatures and humidities experienced by developing immatures and adults within nests fluctuated markedly (Packer et a!., 1989a The finding of highly significant linkage disequilibrium, even between only two of the loci, is interesting because values of D for allozyme loci are typically close to zero in outbred populations unless the loci are tightly linked (Hedrick, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…This population is of particular interest because of its extremely low level of sociality (Packer et aL, 1989a;Packer, submitted). A. striata is a member of the bee family Halictidae, a group well known for its wide range of social organisation and multiple origins of eusociality (Michener, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Halictids are important bees for studies of social evolution because they show enormous intra- (Sakagami and Munakata, 1972;Yanega, 1988;Eickwort et al, 1996;Richards, 2000;Soucy, 2002) and inter-specific variation in social behavior. Variation in social behavior within species is often linked with altitude and latitude such that populations at high elevation and latitude tend to be solitary, while populations at lower elevation and latitude tend to be eusocial (Sakagami and Munakata, 1972;Packer et al, 1989;Eickwort et al, 1996;Soucy, 2002;Soucy and Danforth, 2002). Diversity in social behavior among species was often thought to be due to frequent independent origins of eusociality in halictids (Eickwort, 1986) but recent molecular studies within and among genera of Halictinae have suggested that reversals from eusociality to solitary nesting may be common (Packer, 1997;Danforth, 1999;Danforth et al, 1999Danforth et al, , 2003Brady et al, 2006).…”
Section: Diversity In Social Behaviormentioning
confidence: 99%
“…1) suggests a low frequency of multiple foundress association. For discussion of the limited evidence for multiple foundress nests see Packer et al (1989a).…”
Section: Description Of Colony Cyclementioning
confidence: 99%